The Competition of Local and Product of China in Meeting Consumer Demand Based in Gembrong Market Jakarta Timur - Sundari, Sri; Legionosuko, Tri; Asmat, Usnanta Prasetya; Syafarudin, Afriapollo (International Review of Management and Marketing, 2019)
The demand of customer raises the competitiveness of local and Chinese products in the Gembrong market East Jakarta, based. In the case of ACFTA, Indonesia’s strategy has main focus in improving the quality of human resources and labor productivity. Data is collected by observation, interviews, and documentation. The data obtained and analyzed according to the actual conditions, then each actual conditions element is combined in order to produce a conclusion. The government has strengthen the domestic market by implementing compulsory Indonesian National Standards (SNI) for industrial products, trade policy such as the application of Producer Importers (IP) and Registered Importer (IT) the application of trade defends optimizes the increasing of domestic product usage ( P3DN) in all lines of life and economic activities. Keywords: Gembrong Market, Consumer Demand, Local and Chinese Product Competition JEL Classification: M3